The Experiential Paradoxes of Pain. - LEDER, DREW (Journal of Medicine & Philosophy, 2016)
Pain is far more than an aversive sensation. Chronic pain, in particular, involves the sufferer in a complex experience filled with ambiguity and paradox. The tensions thereby established, the unknowns, pressures, and oscillations, form a significant part of the painfulness of pain. This paper uses a phenomenological method to examine nine such paradoxes. For example, pain can be both immediate sensation and mediated by complex interpretations. It is a certainty for the experiencer, yet highly uncertain in character. It pulls one to the present but also projects one outward to a feared or desired future. Chronic pain can seem located in the body and/or mind; interior to the self, or an alien other; confined to a particular point and/or radiating everywhere. Such fundamental paradoxes, existential and epistemological, can challenge those living with long-term pain.